Modulatory influence of melatonin on apical periodontitis in Wistar rats fed a high-fat diet - Santos, Rodrigo Martins Dos [UNESP]; Machado, Nathalia Evelyn da Silva [UNESP]; Cantiga-Silva, Cristiane [UNESP]; Belardi, Bianca Elvira [UNESP]; Tsosura, Thais Verônica Saori [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Tessarin, Gestter Willian Lattari [UNESP]; Mattera, Maria Sara de Lima Coutinho [UNESP]; Nobumoto, Ana Carla Thalez Ywabuchi [UNESP]; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Matsushita, Doris Hissako [UNESP] (Elsevier, 2023)
OBJECTIVE: This study aimed to evaluate the influence of high-fat diet (HFD) and melatonin (MEL) treatment on the progression of inflammation and alveolar bone resorption (ABR) in rats with AP. DESIGN: Forty male Wistar rats were divided into four groups: apical periodontitis (AP), HFDAP, APMEL and HFDAPMEL. The animals were fed an HFD or standard diet for 107 days. On the 7th day, the rats were subjected to AP, and after 70 days, the rats in the MEL groups were treated with MEL for 30 days. Post treatment, the animals were euthanized, and their jaws were retrieved for evaluation of bone resorption, intensity of the inflammatory response, and immunohistochemical analysis including tartrate-resistant acid phosphatase (TRAP) and interleukin-1β (IL-1β) levels and tumor necrosis factor (TNF)-α expression. RESULTS: The APMEL group showed reduction in the inflammatory infiltrate and IL-1β expression relation to HFDAP, while the TNF-α levels did not differ among the groups. The HFDAP group showed an increase in the ABR. MEL reduced the TRAP levels in the APMEL and HFDAPMEL groups. CONCLUSIONS: while MEL could reduce TRAP levels in the APMEL and HFDAPMEL groups, the reduction in the HFDAPMEL group was smaller than that in the APMEL group, demonstrating that the interaction between AP and HFD decreased the anti-resorptive effects of MEL.